The Palm-leaf Manuscripts in Thosaphon Kantha of Phra That Chom Phrik Temple in Tha Wang Pha District and Pong Kham Temple in Phu Phiang District, Nan Province: Transliteration, Translation and Comparison - Thammawuttho (Dipinta), Phramaha Srawut; NA NAN, Phra Rajanandhawachrabandit; Kerdchor, Chamnarn (Mahachula Academic Journal, 2025)
The objectives of this thesis were: (1) to study the history of The Palm-Leaf Manuscripts in Dasaporn Kantha of Phra That Chom Phrik Temple in Tha Wang PhaDistrict and Pong Kham Temple in Phu Phiang District, Nan Province; (2) to transliterateand translate of The Palm-Leaf Manuscripts in Dasaporn Kantha of Phra That Chom Phrik Temple in Tha Wang Pha District and Pong Kham Temple in Phu Phiang District,Nan Province; and (3 ) to compare of The Palm-Leaf Manuscripts in Dasaporn Kanthaof Phra That Chom Phrik Temple in Tha Wang Pha District and Pong Kham Temple inPhu Phiang District, Nan Province: Transliteration, Translation and Comparison in NanProvince. This was a scriptural research, analyzing data by describing the content. Theresults of the research study found that: This study examines two palm-leaf manuscripts of the Khandha Thosaphon text: the Wat Phra That Chom Phrik version, inscribed by Nan Techa in 1920 (B.E. 2463), now 105 years old, comprising 8 leaves and 20 pages; and the Wat Pong Kham version, inscribed by Phra Bunrat in 1903 (B.E. 2446), now 122 years old, comprising 12 leaves and 24 pages. The physical dimensions are as follows: the Wat Phra That Chom Phrik manuscript measures 4.5 cm wide, 45 cm long, and 1.5 cm thick, while the Wat Pong Kham manuscript is 5 cm wide and 47 cm long. In terms of transcription and translation, the researcher successfully transcribed and translated 17 pages of the Wat Phra That Chom Phrik manuscript and 19 pages of the Wat Pong Kham manuscript, as detailed in Chapter 3. The comparative analysis of the two manuscripts focuses on four aspects: (1) Form and use: The script in the Wat Phra That Chom Phrik manuscript is clearer and more aesthetically pleasing than that of Wat Pong Kham, though both are seldom used in preaching. (2) Structure and main content: Both manuscripts share similar introductory verses expressing reverence to the Buddha. (3) Doctrinal themes: They contain comparable moral teachings, notably the law of karma, the four Brahmavihāras, and the principle of heedfulness. (4) Aesthetic literary qualities: Both manuscripts exhibit four literary flavors (rasas): 1 )Sauvarjanee (praise of beauty), seen in descriptions of Queen Phusati’s grace; 2) Nareepramod (romantic delight), evident in King Sanjaya’s affection for Queen Phusati; 3) Sallapangabhisaya (compassionate dialogue), shown by Queen Phusati’s concern for her children and subjects; 4)Santhatavohara (effective rhetoric), employing powerful, clear expressions to convey moral ideas, such as when Queen Phusati desires to benefit beings by establishing a charity hall. 5) Lastly, the manuscripts demonstrate connections with the Tipitaka and its commentaries, reflecting core Buddhist teachings.